O desenvolvimento de habilidades importantes para o século XXI em praticantes de e-sports: colaboração e competitividade no jogo Counter-Strike - Hessel, Luis Felipe Di Grado (2022)
This research inserted in the field of Technology of Intelligence and Digital Design (TIDD) aims to identify how 21st century skills, such as communication, collaboration, critical thinking, problem solving, creativity and innovation, are developed with the practice of gamers in electronic sports scenarios, more specifically in the game Counter-Strike, which is one of the most popular modalities in Brazil and in the world. A category of entertainment, which, like digital culture – lifestyle linked to technologies, grows, and increasingly gains great space and popularity in our society. E-sports already attract more spectators and fans than many sports. Allied to the digital culture and communities that involve these electronic sports, practitioners, parents and teachers can find in this activity a wide opportunity for the teaching and learning processes and for the development of skills considered important for the 21st century. This dissertation presents some points to understand which are these important skills for the world of work and how electronic sports collaborate for their development. The author uses his twenty years of experience as a player, coach, narrator, commentator, and analyst in the competitive Counter-Strike gaming landscape to help identify these skill development opportunities. The study presents comments on the game in question to understand how the skills required for the 21st century, such as competitiveness and collaboration, as well as communication, critical thinking, problem solving, creativity and innovation, occur during sports practice. This is qualitative research and follows a bibliographic, narrative and exploratory path. The conclusions infer that the practice of E-Sports, in which collaboration and competitiveness occur in parallel, can potentially contribute to the development of different skills required in the scenario of current and future professional occupations